THE COGNITIVE DICHOTOMY OF "SHAME" IN KARAKALPAK AND ENGLISH: A COMPARATIVE STUDY OF "FACE" METAPHORS - Khudaybergenova, Turdigul Kalbayevna (SCIENCE and SOCIETY, 2026)
This article compares the linguocognitive nature of "Shame" in Karakalpak and English linguistic worldviews using "face" metaphors. The research highlights a cognitive dichotomy: English "face-saving" expressions focus on individual reputation, while Karakalpak "face-blackening" idioms reflect collective honor